Persisting Pranata Mangsa: The Challenges of Traditional Knowledge Practices in the Era of Climate Crisis - Ghofur, Mohammad (Jurnal Pemikiran Sosiologi, 2024)
For decades, smallholder farmers in the karst areas of Gunungkidul Regency, Yogyakarta, have endured precarious livelihoods shaped by environmental limitations. Scarce surface water, the absence of technical irrigation, rugged topography, and poor soil fertility present persistent challenges. Nevertheless, farmers continue to adapt using local knowledge systems—most notably Ngawu-awu, a practice rooted in the traditional Pranata mangsa agricultural calendar. Since the early 2000s, the intensifying climate crisis has further disrupted this ecological rhythm, forcing smallholders to rethink their livelihood strategies. This study examines how smallholder farmers navigate the changing climatic conditions while attempting to sustain Ngawu-awu practices. Three key aspects are explored: first, the use of Pranata mangsa to anticipate seasonal rainfall; second, the growing mismatch between this traditional calendar and the erratic patterns of the climate crisis; and third, the coping strategies employed by farmers amid this dissonance. Drawing on a case study approach, the research identifies four expressions of local knowledge: attentive reading of natural signs, collective experimentation and learning, intergenerational knowledge transmission, and communal resilience through reflective adaptation. These practices illustrate how cultural endurance and ecological sensitivity intersect in times of uncertainty.